Influence of ultrasonic vibration on tin coated Biomedical TI-13Zr-13Nb Alloy - Arman Shah Abdullah (N/A, 2015)
Influence of ultrasonic vibration on tin coated Biomedical TI-13Zr-13Nb Alloy by Arman Shah Abdullah